IMPLEMENTASI PRINSIP PRINSIP ASWAJA DALAM PENDIDIKAN UNTUK MEMPERKOKOH KARAKTER BANGSA DAN MEWUJUDKAN ENTITAS NKRI - M. Lukman Hakim; Mohamad Taufik Hidayat; MUh. Sifa (Al-Fikr: Jurnal Pendidikan Islam, 2022)
Indonesia is a very diverse country, starting from different religions, ethnicities, languages ​​and customs. In the current industrial 4.0 era, radicalism is growing rapidly several times to shake the integrity of the unitary state of the Republic of Indonesia, Indonesia with a majority Muslim population with the direction of ASWAJA (Ahlu al-Sunnah wal-Jama'ah) are people who are always guided by the Sunnah of the Prophet Muhammad. SAW (Salallahu Alaihi Wassalam), the way of the companions of the Prophet in matters of religious aqidah, outward deeds, and morals of the heart. The ASWAJA group are the survivors. The term "Sunnah" in ASWAJA refers to the instructions of the Prophet Muhammad and his companions, both knowledge, aqidah, words, and practices, namely the Sunnah which is used as a guide. ASWAJA values ​​such as: “tawassuth” (moderate), “tawazun” (balanced), “tasamuh” (tolerant), and “i'tidal” (fair) become very important to be applied more massively and planned in education for prepare the next generation. The method and approach used in this study is descriptive qualitative, with data obtained from literature studies, discussions, and seminars on ASWAJA values. Furthermore, the material in this article is focused on ASWAJA values ​​that must be applied in education and how to implement ASWAJA values ​​strategies and methods to strengthen the nation's character in realizing the Unitary State of the Republic of Indonesia (NKRI).